Service restoration with the presence of distributed generation in a distribution system: article / Masruddin Samsuddin - Samsuddin, Masruddin (2009)
This project studies the influence of distributed generation during service restoration and to identify the optimal network reconfiguration at the power distribution systems for loss reduction and voltage profile improvement under fault condition with the installation of distributed generation. It is assumed that after the occurrence of fault at particular section of a distribution network, the loads get disconnected and are left unsupplied. Service should be restored to the affected loads through a network reconfiguration procedure. The simulation was conducted by applying three phase fault at an identified location. In this study, network reconfiguration was implemented using the TOPO application in the power system simulation programmed for planning, design and analysis of distribution system (PSS/Adept). This application determines the optimal sectionalizing-tie switch pairs based on minimum losses configuration and at the same time, all nodes are assured for the supply. The location of the distributed generation was identified by finding the minimum bus voltage. The results show that installing distributed generation at the suitable location with appropriate sizing has able to provide lower loss level and higher voltage profile in fault condition as compared to that obtained before installed distributed generation and network reconfiguration. The proposed study was conducted on the IEEE 69 bus distribution system.